2018
DOI: 10.7567/jjap.57.061302
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature bonding of epitaxial layer to carbon-cluster ion-implanted silicon wafers for CMOS image sensors

Abstract: We propose a fabrication process for silicon wafers by combining carbon-cluster ion implantation and room-temperature bonding for advanced CMOS image sensors. These carbon-cluster ions are made of carbon and hydrogen, which can passivate process-induced defects. We demonstrated that this combination process can be used to form an epitaxial layer on a carbon-cluster ion-implanted Czochralski (CZ)-grown silicon substrate with a high dose of 1 ' 10 16 atoms/cm 2 . This implantation condition transforms the top-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 56 publications
(91 reference statements)
4
17
0
1
Order By: Relevance
“…Second, our previous study demonstrated that pn-junction leakage current of pn-junction diode dramatically decreased by combination of both hydrocarbon–molecular implantation and surface activated wafer bonding (SAB) techniques compared to without SAB [65,66]. The pn-junction leakage current determined some factors such as metallic impurity contamination in space-charge region and interface state defect in device isolation region.…”
Section: Gettering Technology Design For Back-side-illuminated Cmomentioning
confidence: 99%
See 2 more Smart Citations
“…Second, our previous study demonstrated that pn-junction leakage current of pn-junction diode dramatically decreased by combination of both hydrocarbon–molecular implantation and surface activated wafer bonding (SAB) techniques compared to without SAB [65,66]. The pn-junction leakage current determined some factors such as metallic impurity contamination in space-charge region and interface state defect in device isolation region.…”
Section: Gettering Technology Design For Back-side-illuminated Cmomentioning
confidence: 99%
“…Third, we demonstrated that the hydrogen out-diffused to silicon epitaxial layer (device active region) from hydrogen storage in hydrocarbon–molecular–ion projection range during the heat treatment [35,65,66]. This hydrogen of out diffusion amount is 10 12 to 10 13 cm −2 measured by SIMS after heat treatment [70].…”
Section: Gettering Technology Design For Back-side-illuminated Cmomentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, vacuum deposition of metal atoms on a silicon surface saturated with restrictive molecules was used in [12]. Another method is the direct implantation of carbon and hydrogen with subsequent temperature annealing [13]. As a result, it is possible to obtain improvements in the characteristics of silicon structures [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Another method is the direct implantation of carbon and hydrogen with subsequent temperature annealing [13]. As a result, it is possible to obtain improvements in the characteristics of silicon structures [13][14][15]. However, in the presence of a significant number of linear defects, such techniques can cause mechanical damage to the surface [16].…”
Section: Introductionmentioning
confidence: 99%